Selectivity and permeation of alkali metal ions in K+-channels. - Furini, S; Domene, C (2011)
Ion conduction in K(+)-channels is usually described in terms of concerted movements of K(+) progressing in a single file through a narrow pore. Permeation is driven by an incoming ion knocking on those ions already inside the protein. A fine-tuned balance between high-affinity binding and electrostatic repulsive forces between permeant ions is needed to achieve efficient conduction. While K(+)-channels are known to be highly selective for K(+) over Na(+), some K(+) channels conduct Na(+) in the absence of K(+). Other ions are known to permeate K(+)-channels with a more moderate preference and unusual conduction features. We describe an extensive computational study on ion conduction in K(+)-channels rendering free energy profiles for the translocation of three different alkali ions and some of their mixtures. The free energy maps for Rb(+) translocation show at atomic level why experimental Rb(+) conductance is slightly lower than that of K(+). In contrast to K(+) or Rb(+), external Na(+) block K(+) currents, and the sites where Na(+) transport is hindered are characterized. Translocation of K(+)/Na(+) mixtures is energetically unfavorable owing to the absence of equally spaced ion-binding sites for Na(+), excluding Na(+) from a channel already loaded with K(+).